Late-onset popliteal artery pseudoaneurysm secondary to implant migration in a pediatric patient: a case report and surgical management - Duymaz, Senanur; Duymaz, Burak; Gursan, Onur; Kosay, M. Can (Frontiers in Pediatrics, 2025)
IntroductionPopliteal artery pseudoaneurysms are rare but potentially life-threatening complications following orthopedic procedures, particularly osteotomies. These pseudoaneurysms, characterized by a hematoma caused by disruption of the arterial wall and contained by surrounding tissues rather than all arterial layers, can cause severe ischemic damage if not promptly diagnosed and treated. Early detection and timely surgical intervention are critical to prevent catastrophic outcomes such as thrombosis, embolization, or limb loss. This case highlights the challenges in diagnosing and managing a delayed popliteal artery pseudoaneurysm caused by implant migration in a pediatric patient.Case PresentationA 15-year-old male patient with cerebral palsy presented with sudden, severe knee pain and localized swelling around the knee joint. These symptoms occurred two years after he underwent a distal femoral extension osteotomy with lateral plate fixation. Initial imaging studies were inconclusive, suggesting possibilities such as soft tissue sarcoma or hematoma. However, an incisional biopsy unexpectedly revealed a pseudoaneurysm cavity adjacent to the popliteal artery. Further imaging identified that the distal screws of the femoral plate had migrated posteriorly due to femoral deformity, causing direct irritation and injury to the artery.Surgical InterventionAn urgent multidisciplinary surgical approach was implemented. The procedure began with femoral artery clamping to control bleeding, followed by excision of the pseudoaneurysm cavity. A saphenous vein graft was harvested and interposed to repair the damaged segment of the popliteal artery. To eliminate the source of irritation, the screws were removed. Postoperative ultrasonography confirmed successful arterial repair, with no signs of thrombosis or recurrence. The patient was mobilized early and discharged with an antiplatelet regimen, followed by regular clinical monitoring.ConclusionThis case emphasizes the importance of routine follow-up in pediatric patients with orthopedic implants, as skeletal growth and deformity progression can lead to implant migration and serious vascular complications. The delayed diagnosis underscores the need for heightened clinical suspicion and comprehensive imaging in patients with unusual postoperative symptoms. Early recognition and timely multidisciplinary surgical intervention are crucial for preventing life-threatening vascular injuries. This case also highlights the necessity of individualized implant removal planning in growing patients to avoid similar complications.